Vaccinating against COVID-19: The Correlation between Pro-Vaccination Attitudes and the Belief That Our Peers Want to Get Vaccinated - Darie Cristea; Dragoș-Georgian Ilie; Claudia Constantinescu; Valeriu Fîrțală (Vaccines, 2021)
This study verifies whether there is a strong correlation between the pro-vaccination, against COVID-19 attitude of the respondents and their belief that most of those around them want to be vaccinated against COVID-19. For this purpose, we analyzed data from a sociological survey conducted in April 2021 in Romania. The sample size was of 1001 respondents, the selection process was randomized and the population included in the sample is representative of the socio-demographic structure of Romania. The tool used to collect the data was CATI (telephonic interview). In order to test the existence of these correlations we performed the following tests: Chi-Square test, Kendall τ, Spearman ρ tests and Freeman’s z-test. The pro-vaccination attitude strongly correlates with the perception of subjects that their primary group accepts vaccination and even correlates with the perception that the general public is rather pro-vaccination. The vaccination decision is closely linked to the social relations system and the rules of the community in which the subject lives. In this paper we discuss the correlation between attitude and belief, not the existence of a causal relation between the two of them.